A multi-species, process based vegetation simulation module to simulate successional forest regrowth after forest disturbance in daily time step hydrological transport models. (1st August 2008) - Putz, G; MacDonald, J Douglas; Prepas, E E; Kiniry, J R
Abstract : To simulate the effects of tree harvest on boreal forest catchment hydrology, the vegetation growth model within the soil and water assessment tool (SWAT) must reproduce the successional stages of forest reestablishment. The agricultural land management alternatives with numerical assessment criteria (ALMANAC), a multi-species growth model, was modified to simulate vegetation regeneration on forest sites after harvest (ALMANACBF ). The model uses similar principles of vegetation growth as the current vegetation model in SWAT, and input requirements are consistent with typical forest inventory databases. This article describes the algorithms integrated into the ALMANACBF model to simulate successional stages in forest growth, provides initial estimates of parameters required to simulate multi-species forest succession, and presents examples of the type of variability in vegetation growth scenarios that these algorithms can reproduce. The model structure and modelling approach shows promise as a tool for foresters to evaluate how patterns and timing of forest management activities influence forest watershed hydrology.